Representaciones sociales en la prensa escrita sobre el consumo de drogas - Torres Valladares, Silvia Gabriela (2016)
The purpose of this research project was to determine. The Social Representation in the newspaper El Comercio and La Hora, in relation to the handling of information sources Topics about the Drugs. This paragraph used the category of Social Representations. The methodology used in this researching was content analysis, taking as example publications two national print media within six months with the last four weeks when the field work is concerned, obtaining a total of 36 Journalistic Notes. Were used categories: owner, date, subject, genre, sources, section, scope, content and latent content manifest. Among the results highlighted in this child Project Management Sources BY instance of journalists, who give them centrality of authorities such as the police and armed forces. It is necessary that the UN journalist Perform comprehensive analysis on this type of phenomena occurring in society. This research contributes to the analysis the construction of Journalistic Publications and what social representations are built around the theme of drugs.